2011
DOI: 10.1080/10286020.2011.566868
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect and neurotoxicity of S-(+)-deoxytylophorinidine, a new phenanthroindolizidine alkaloid that interacts with nucleic acids

Abstract: Phenanthroindolizidine alkaloids are a family of plant-derived compounds with significant antineoplastic activity as well as other effects like antiamebicidal, antiviral, and anti-inflammatory activities. The specific biomolecular targets of these compounds have not yet been clearly identified. S-(+)-Deoxytylophorinidine (CAT) is a new phenanthroindolizidine alkaloid, originally extracted from the roots of Tylophora atrofolliculata and Tylophora ovata. Potent anticancer activity was observed in vitro and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Since 1 was confirmed to interact with DNA and RNA [28], [29], what will happen to the down-stream cellular processes? Based on previous reports that PI3K and MAPK signaling transduction pathways played a fundamental role in the apoptosis induced by DNA-damaging drugs, we investigated the influence of deoxytylophorinine derivatives on these two signaling transduction pathways.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 1 was confirmed to interact with DNA and RNA [28], [29], what will happen to the down-stream cellular processes? Based on previous reports that PI3K and MAPK signaling transduction pathways played a fundamental role in the apoptosis induced by DNA-damaging drugs, we investigated the influence of deoxytylophorinine derivatives on these two signaling transduction pathways.…”
Section: Resultsmentioning
confidence: 99%
“…1 could interact with DNA and RNA and concomitantly block the process of transcription to produce the anticancer effects in Liu's research [28], [29]. And high concentrations of 1 could induce cell apoptosis (Figure S1).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In other studies, the trimethoxy indolizidine alkaloid designated CAT ( 18 , Figure 5A; (+)‐13a‐( S )‐deoxytylophorinidine) exerted significant antitumor activity in vitro and in vivo 60,61 . In addition, PF403 ( 19 , Figure 5A; 3‐ O ‐desmethyl‐13a‐( S )‐deoxytylophorinidine), one of three monodesmethyl metabolites of 18 , showed stronger antiproliferative activity than the parent compound or the other two metabolites in several tumor cell lines 62 .…”
Section: Bioactivities Of Indolizidine Alkaloidsmentioning
confidence: 89%
“…The anti-tumor activity of CAT is primarily attributed to its ability to intercalate into AT-repeated base pairs in double-helical DNA sequences. Further studies have shown that CAT potently suppresses the proliferation of common cancer cell lines such as HepG2 and A549 cells, with an IC 50 of approximately 10 −7 mol/L [11,12]. CAT was susceptible to metabolism by rat liver microsomes and its three major monodesmethyl metabolites were synthesized recently [13], among which 3-O-desmethyldeoxytylophorinine (S-4, Fig.…”
Section: Introductionmentioning
confidence: 98%